La Industria lítica Del Núcleo Urbano Maya de la Blanca, Petén, Guatemala Tecnología y Tipología. - Torres Marzo, Ricardo (Paris Monographs in American Archaeology Ser., 2021)
The ancient Maya used mainly stone tools, made of either ground stone and chipped stone, to achieve their extraordinary development. This book presents the techno-typological analysis of lithic materials from La Blanca, located in the heart of the Southern Lowlands, which was mainly inhabited during the Late Classic and Terminal Classic periods.